Spore germination and early gametophyte development of Platycerium wandae (Polypodiaceae) from Papua, Indonesia - TITIEN NGATINEM PRAPTOSUWIRYO (Society for Indonesian Biodiversity, 2017)
Abstract. Praptosuwiryo TNg. 2017. Spore germination and early gametophyte development of Platycerium wandae (Polypodiaceae) from Papua, Indonesia. Biodiversitas 18: 175-182. Studies on gametophyte development in ferns are very important, as the data generated is often useful for supporting taxa delimitation in ferns and fern-allies. This data is also very important for understanding the ecology, reproductive biology, evolution and distribution of ferns. The study reported here aimed to develop a deeper understand of morphogenesis in the fern Platycerium wandae Racib. by investigating the process of spore germination and early gametophyte development of the species on natural media. Fresh spores of P. wandae were germinated in a mixed media consisting of minced roots of Cyathea contaminans and charcoaled rice hulls (1: 1) under green house condition. Spores of P. wandae are monolete, ellipsoid, non-chlorophyllous, dark brown, and lacking perine. Spores germinated between 7 to 14 days after sowing (DAS). Spore germination of P. wandae is of the Vittaria-type and the prothallial development is of the Aspidium-type, characterized by early development of unicelullar trichomes (30-40 DAS). Only unisexual gametophytes were observed at 60-80 DAS. New data is provided concerning the morphogenesis of P. wandae from Papua, Indonesia, on natural media. The findings are relevant to reproductive biology, would contribute to establish an efficient ex situ propagation strategies for the conservation of epiphyitic ferns and to facilitate further in situ studies of gametophyte ecology. Keywords: Gametophyte development, Platycerium wandae, spore germination, staghorn fern